An Analysis of the Urgency of Halal Certification for Chicken Meat Sellers at Lakessi Market - A. Haerunnisah Azizah; Islamul Haq; Damirah Damirah; Syahriyah Semaun; Andi Bahri (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to analyze the practice of selling broiler chicken at Lakessi Market in Parepare City, map the halal product assurance system at the trader level and consumer perceptions, and assess the urgency of halal certification. This study used a qualitative method with a descriptive case study approach. Primary data were collected through observations and interviews with 20 informants consisting of 8 broiler chicken sellers, 10 consumers, and 2 government agency representatives, with data analysis conducted inductively. The results show that sales practices generally follow two patterns: supply from slaughterhouses considered trustworthy or independent slaughtering with efforts to follow Islamic slaughter procedures, basic hygiene aspects (cleanliness of equipment, covering meat with plastic, use of ice) are also considered. However, halal assurance in the field is still predominantly based on trust and visual verification by consumers, so that halal assurance cannot be fully assured without certification. The urgency of halal certification is highly assessed to strengthen regulatory certainty, consumer protection, and market confidence, but compliance is hampered by limited understanding of procedures and concerns about costs, so government assistance is a key need.